Rancang Bangun Aplikasi E-learning Berbasis Web Untuk SMK Menggunakan Metode Extreme Programming - Tresnawati, Dewi; Ardiansyah, Ryan (Institut Teknologi Garut, 2025)
The development of information and communication technology has brought significant changes in the field of education, where learning is no longer confined to conventional classrooms. Global trends indicate that e-learning has become one of the main solutions to address the challenges of modern education, particularly with the growing demand for flexible, interactive, and accessible distance learning for both students and teachers. In Indonesia, the implementation of e-learning is increasingly encouraged by government policies aimed at school digitalization. However, in practice, many educational institutions still face obstacles such as limited infrastructure, lack of system integration, and low utilization of technology in teaching and learning activities. Based on these conditions, this research focuses on the development of a web-based e-learning system specifically designed for SMK Setia Bhakti Garut. The application was developed using the Extreme Programming methodology to ensure flexibility and efficiency throughout the development process. The system includes key features such as material management, assignments, online examinations, interactive learning videos through the WordPress H5P plugin, student group management, and activity notifications. The development process began with user requirements analysis using a user story approach, followed by system design, program implementation, and testing to ensure functionality. The results of black-box testing indicate that all functional components of the system operate as expected according to the defined functional requirements. Moreover, the integration of H5P content within WordPress provides teachers with the flexibility to design interactive multimedia-based learning materials.